Is Child Like Parent? Educational Attainment and Ethnic Origin - Ira N. Gang; Klaus F. Zimmermann (Rutgers University, Department of Economics, 1999)
The speed at which immigrants assimilate is the subject of debate. Human capital formation plays a major role in this discussion. This paper compares the educational attainment of second generation immigrants to those of natives in the same age cohort. Evidence using a large German data set suggests ethnicity does matter: the size of the ethnic network has a positive effect on educational attainment, and a clear pattern is exhibited between countries-of-origin and educational attainment even in the second generation. For the children of the foreign-born, parental schooling plays no role in making educational choices. However, for Germans, contrary to the general findings in the literature, there is a statistically significant difference in favor of fathers education over mother's education.
Keywords: I21; J15; J62; 330; assimilation; education; ethnicity; migration; second generation migrants